ANALISIS HUBUNGAN MARKETING MIX TERHADAP LOYALITAS KONSUMEN PADA KOFFIELOTS COFFEE & EATERY - AGNES MONICA BR SEMBIRING; COKORDA GEDE PUTRA YUDISTIRA; LILY MARHENI (Universitas Mahasaraswati K. Mataram, 2024)
Marketing mix is one of the marketing strategies to convey information widely, introduce a product of goods and services, stimulate consumers to give and even create personal preferences for the image of a product. It can be seen that Koffielots Coffee & Eatery experienced a significant decline in sales from January to December. In January, sales were recorded at Rp 17,134,500 with a sales percentage reaching 12%. However, in December, sales dropped drastically to Rp 7,814,500 with a sales percentage of only 5%. The type of research data uses a quantitative approach. The data analysis method uses multiple linear regression. The study shows that the variables Product (X1), Price (X2), Promotion (X3), and Location (X4) have a significant positive effect on Consumer Loyalty (Y). This is evidenced by the positive and significant regression coefficient, as well as the high Adjusted R Square value (80.9%). The high correlation value (ranging from 0.804 to 0.868) indicates that an increase in each variable will tend to increase consumer loyalty in one direction